Modeling of the flow time series for a short-term hydrological forecast - Tomasz Jarosław Siuta (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: Within this article an example of an effective approach to real-time, short term forecast of flood rates within Vistula river differential catchment was presented. This forecast is based on flow rates time series measured at the water gauge input and output cross sections of the river system with a daily delay without taking into account any precipitation data.